Snakehead Fish Extract in Increasing Skin Collagen & Fibroblasts - Maharani Frima Setyowiranti; I Gusti Nyoman Darmaputra (Postgraduate, University of Mataram, 2023)
This study aim is to gain a deeper understanding of the mechanisms by which snakehead fish extract affects the skin, opening doors for the development of more effective and natural skincare products. The study employs a systematic literature review method using PRISMA strategy, identifying 156 relevant articles through platforms such as PubMed, Google Scholar, Scopus, SINTA, spanning from 2018 to 2023. Findings encompass increased VEGF production and NO levels with snakehead fish extract dosages, wounds healing potential of honey and snakehead fish skin combination in hydrogel formulations, increased fibroblast counts, reduced skin erythema, and decreased wound crust formation. Additionally, marine collagen exhibits promise in skin healing and bone repair. Collagen supplements, whether oral or topical, also prove beneficial in delaying skin aging. The study reveals crucial insights into the potential of snakehead fish extract in skincare and wound healing, supporting the development of more effective and natural skincare products.